Implementation of Psychodynamic Multifamily Groups for Severe Mental Illness: A Recovery-Oriented Approach - Maone, Antonio; D'Avanzo, Barbara; Russo, Federico; Esposito, Rita Maria; Goldos, Bozena Lucyna; Antonucci, Alessandro; Ducci, Giuseppe; Narracci, Andrea (Frontiers in Psychiatry, 2021)
Background Among Family-Based Services for the treatment of severe mental illnesses, multi-family models gained particular attention, given the potential usefulness of mutual feed-backs, motivation and encouragement among families. Methods The Psychodynamic Multi-Family Group Model has been proposed since 1997 in some Community Mental Health Services in Rome, and data have been collected since 2015. A total of 794 individuals attended the meetings in the period 2015-2019. Results Eighty-six percent of those who started, attended more than one meeting. The mean of occurrences of participation among patients was 18.6, among mothers 25.6 and among fathers 21.6. The 794 participnats belonged to 394 families, among which 180 comprised only the patient, 76 only parent(s) or other close person(s), and 183 comprised parent(s) or close person(s) with the patient. Patients participating alone were older than those of families who participated as a whole. Families including the patient showed the longest duration of attendance and were more represented when the patient had a diagnosis of schizophrenia. Even families who had been attending the multifamily groups since a long time maintained a high rate of attendance. The high number of patients who attended alone suggests that such participation corresponds to a self-perceived need of open and free setting facilitating sharing of problems and solutions. Conclusions Multifamily groups represent a setting where patients can meet with other people and professionals in a free still finalized way, and with not strictly therapeutic objectives. The good tenure of the interventions, the high participation, and the feasibility in the long-term suggest that multifamily groups should be available to larger numbers of patients and families in as many services as possible.